BMKG’s Communication: A Systematic Literature Review - Kasih, Pustika Chandra; Susana, Mutia; Sarwesti, Sarwesti; Soraya, Rachmi; Bhirawan, Bio (Jurnal Komunikasi, 2024)
Communication is important in the public sector organization and plays a critical aspect in modern government management. Therefore, the public sector is currently competing to improve appropriate communication strategies as an effort to increase reputation and credibility. This research was prepared using a systematic literature review method regarding communication between public sector agencies of the Meteorology, Climatology and Geophysics Agency (BMKG). The aim of this research is to provide a comprehensive overview of the development of communication research carried out so far with a research focus on agency communication. This research method involves a systematic search in the academic database of national journals via Google Schoolar on 18 articles that have been selected using keywords related to BMKG communication in the period 2018-2023. As a result, the most articles in this journal will be published in 2023 (33%), with qualitative research methods (56%) being the highest, with the highest journal accreditation being Sinta 4 (33%). In conclusion, the writing of scientific studies that focus on the field of communication in the BMKG government agency still needs to be developed further considering that the field of communication is experiencing very rapid development so that this public sector agency really needs to carry out updates in the field of communication which have been carried out in recent years.